BUILDING A PEOPLE'S ECONOMIC ECOSYSTEM THROUGH THE SYNERGY OF COOPERATIVES AND MSMES FOR GOLDEN INDONESIA 2045 - Subagyo, Ahmad; Akyuwen, Roberto; Wibowo, Martino; Nofitasari, Diah; Kurniawan, Muhammad Arif (International Journal of Research -GRANTHAALAYAH, 2024)
This article analyzes strategies for building a people's economic ecosystem through optimizing synergy between cooperatives and MSMEs in order to realize the vision of Golden Indonesia 2045. Using a literature analysis and secondary data approach, this study explores the concept of the people's economic ecosystem, the role of cooperatives, the challenges and opportunities of MSMEs, and the synergy strategy between the two sectors. The implementation of the grand theory of growth and equity was also discussed as a policy foundation. The results of the analysis show that strengthening the digital ecosystem, optimizing collaboration between stakeholders, and developing a data-based monitoring system are the keys to building effective synergy between cooperatives and MSMEs. This study concludes that with the right strategy, the synergy of cooperatives and MSMEs can be the main driver in creating inclusive and sustainable economic growth towards Golden Indonesia 2045. Policy recommendations include strengthening digital infrastructure, improving cross-sector coordination, and developing a comprehensive evaluation system to support evidence-based decision-making in the development of the cooperative and MSME sectors